Corinth in the First Century AD: The Search for Another Class - Jongkind, Dirk (Tyndale bulletin, 2001)
A consideration of living spaces in ancient Corinth suggests that it is not possible to characterise its society as one made up merely of a very small number of élite alongside vast numbers of non-élite who were extremely poor. The variety of housing suggests the existence of another class.